2014
DOI: 10.3906/biy-1403-29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamines on in vitro anther cultures of carrot (Daucus carota L.).

Abstract: This study examines the influence of the polyamines putrescine and spermidine on the efficiency of androgenesis in anther cultures of 2 carrot cultivars, Kazan F 1 and Narbonne F 1 , and the effect of putrescine on the process of plant regeneration from androgenetic embryos. In the Kazan F 1 variety, an increase in the number of obtained embryos was achieved using each of the 2 polyamines separately and in combination. In contrast, no beneficial effects of polyamines on the efficiency of androgenesis were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Dewi et al (2001) reported that putrescine was more efficient than spermidine and spermine in callus induction and plant regeneration in rice anther culture. Similar observations were reported in several plant species such as P. ginseng (Kevers et al, 2000), G. hirsutum (Sakhanokho et al, 2005), M. charantia (Paul et al, 2009), and Daucus carota (Gorecka et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Dewi et al (2001) reported that putrescine was more efficient than spermidine and spermine in callus induction and plant regeneration in rice anther culture. Similar observations were reported in several plant species such as P. ginseng (Kevers et al, 2000), G. hirsutum (Sakhanokho et al, 2005), M. charantia (Paul et al, 2009), and Daucus carota (Gorecka et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Hoverer, exogenous polyamines can regulate growth and development, including embryogenesis and organogenesis in vitro [40]. Górecka and co-workers [30] examined the effect of the exogenous polyamines, such as putrescine and spermidine supplemented into B5 media, on the efficiency of androgenesis in anther cultures of two carrot cultivars. The authors obtained over 250% more embryos on the medium with the addition of putrescine, and over 40% more on the medium supplemented with spermidine, in comparison to the control.…”
Section: Anther Culturementioning
confidence: 99%
“…Moreover, the promoter role of polyamines in the conversion of somatic embryos or shoot regeneration has been evidenced in several plant species (Górecka et al, 2014;Aydin et al, 2016). Hegazy and Aboshama (2010)…”
Section: Introductionmentioning
confidence: 99%
“…induced direct somatic embryogenesis from bud tissues of date palm through putrescine. Similarly,Kumar et al (2004) applied putrescine and spermidine as an addition to the induction medium of cucumbers, whereasGórecka et al (2014) reported that the addition of putrescine, spermidine, and a mixture of the both to the induction medium had a beneficial effect on the number of embryos in Daucus carota. The results of present study are in line with the above-mentioned studies where the addition of polyamines enhanced somatic embryos formation.ConclusionIt can be concluded from the present findings that theaddition of putrescine in combination with higher concentration of glutamine (EA) has positive embryogenetic potential in date palm cv.…”
mentioning
confidence: 99%